Implantation of urban orchard in the municipality of Cerquilho- SP - Roggieri, Rogério Zanardo; Mattioli, Mateus; Giacomini, Luciana Aparecida (Revista Hipótese, 2019)
The services provided by afforestation in urban centers are immeasurable, either for their social or environmental value. This work aimed to increase the shaded area of a neighborhood located in the municipality of Cerquilho and favor the well-being and quality of life of the population to the environment. Fifty fruit species were planted in total, among native and exotic, by alternating line planting method. During monitoring during the months of may to November 2016 it was observed that 90% of the species were successful in their development and remained healthy.
Keywords: Arborization; Natives; Exotics; Zoocoria